2012
DOI: 10.1108/10662241211214557
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of uncertainty‐avoidance on overall perceived value of a service purchased online

Abstract: Purpose -The aim of this study is to analyze differences in the overall perceived value of a service purchased online, and the consequences for international consumer behavior, taking consumers' uncertainty avoidance as a moderating variable. Design/methodology/approach -A questionnaire was administered to 300 international consumers (150 British and 150 Spanish) who had purchased a service via the internet. SEM was chosen to analyze the effect of uncertainty avoidance on the formation of overall perceived val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 67 publications
4
24
0
1
Order By: Relevance
“…Hypothesis four was left unsupported as time-loss risk was not identified in our data. In line with the suggestions of Kumar and Seth (1998), Munnukka and Järvi (2008), and Sabiote et al (2012), a negative relationship was found between procedural control and perceived risks. The relationship was confirmed as unidirectional as no statistically significant opposite relationship was detected.…”
Section: Conclusion and Theoretical Implicationssupporting
confidence: 84%
See 2 more Smart Citations
“…Hypothesis four was left unsupported as time-loss risk was not identified in our data. In line with the suggestions of Kumar and Seth (1998), Munnukka and Järvi (2008), and Sabiote et al (2012), a negative relationship was found between procedural control and perceived risks. The relationship was confirmed as unidirectional as no statistically significant opposite relationship was detected.…”
Section: Conclusion and Theoretical Implicationssupporting
confidence: 84%
“…Finally, this study explored how buying situation moderates the links between procedural control and purchase-related risks as well as purchase risks and relationship commitment, which were suggested by for example Kumar andSeth (1998), Laios andMoschuris (2001), Munnukka and 20 Järvi (2008), and Sabiote et al (2012). As new task situations are more often subject of higher purchase risks than rebuy situations, it was anticipated that the paths in the research model would be stronger in new task situations (H5 and H10).…”
Section: Conclusion and Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty avoidance was also found to have a moderating effect for both consumer overall perceived value and enjoyment of online purchases (Sabiote, Frías, & Castañeda, 2012). Aykut's (2009) study on e-government acceptance revealed high levels of uncertainty avoidance negatively lowers acceptance.…”
Section: Uncertainty Avoidance (Ua)mentioning
confidence: 98%
“…Untuk pelanggan e-commerce, value yang dirasakan adalah salah satu alasan utama untuk terlibat dalam transaksi online. Para peneliti telah mengamati bahwa sejumlah besar pelanggan e-commerce termotivasi oleh harga yang rendah, yang mempengaruhi sebagian tingkat "give" atau "cost" dari value yang dirasakan (Sabiote et al, 2012;. Tanaka, 1999).…”
Section: Customer Perceived Valueunclassified